A Case of Cardiac Tamponade With Biventricular Heart Failure in the Setting of Systemic Lupus Erythematosus - Sacide S. Ozgur MD; Nida Ansari DO; Yezin Shamoon MD; Sherif Elkattway DO; Rachel Abboud DO; Fayez Shamoon MD (SAGE Publishing, 2024)
Systemic lupus erythematosus (SLE) is an autoimmune disease targeting multiple organs through immune complexes. Pericarditis and pericardial effusions are often encountered; however, cases of biventricular failure are notably less common in the setting of SLE. We report a 43-year-old male patient presenting with cardiac tamponade with biventricular failure in SLE. Our patient with known SLE, not on medication, presented with exertional dyspnea. He had decreased heart sounds, jugular venous distention, and right-sided inspiratory crackles on physical examination. On further investigation, he was found to have a reduced ejection fraction (EF) of 10% to 15% and moderate pericardial effusion. He was treated with immunosuppressive therapy and goal directed medical theraphy (GDMT), with improvement in his EF to 58% 3 months later. This case demonstrates the importance of early recognition of SLE-induced tamponade and the vitality of prompt medical therapy to reduce any further cardiac deterioration.